On methodology for modelling wind power impact on power systems. (14th January 2008) - Soder, Lennart; Holttinen, Hannele
There is a continuous discussion going on concerning the integration cost of wind power. The integration cost can, for example, be defined as the extra costs in the rest of the system when wind power is introduced, compared with the situation without wind power. The result of the studies depends on both parameters and the method used. The aim of this paper is to structure the methods in order to get some understanding on the impact of different modelling approaches. In general, it can be noted that approximations are always needed since the integration of wind power includes so many complexities including stability of power systems, grid codes, market behaviour, uncertainties and trading possibilities. All these items have to be considered in both the wind power case and in the reference case to obtain an estimation of the integration cost.